Wastewater Denitrification with Solid-Phase Carbon: A Sustainable Alternative to Conventional Electron Donors - Dorsa Barkhordari; Jithin Mathew; Basem Haroun; Lars Rehmann; Sudhir Murthy; Domenico Santoro (Nitrogen, 2025)
Nitrate pollution in aquatic environments poses significant environmental and public health issues, mostly due to industrial activities and agricultural runoff. Biological denitrification, the favored method for removing nitrates, typically needs an external carbon source to support microbial processes. Traditional electron donors like methanol, ethanol, and acetate are effective but introduce economic, environmental, and operational challenges such as cost variability, flammability hazards, and excessive residual organic material. Recently, solid-phase carbon sources—like biodegradable polymers and organic agricultural waste—have shown promise as alternatives because they allow for controlled carbon release, improved safety, and enhanced long-term sustainability. This review systematically examines the performance of solid-phase carbon in wastewater denitrification by analyzing peer-reviewed studies and experimental data. The findings suggest that solid-phase carbon sources, including polycaprolactone (PCL) and polyhydroxyalkanoates (PHA), offer stable and extended carbon release, ensuring consistent denitrification effectiveness. Nonetheless, challenges remain, including optimizing biofilm development, balancing carbon availability, and reducing operational costs. Furthermore, the review emphasizes the potential for integrating machine learning in process optimization and highlights the need for more research to enhance the economic viability of these materials. The findings confirm the practicality of solid-phase carbon sources for extensive wastewater treatment and their capability to sustainably address nitrate contamination.